Dying to be men psychosocial, environmental, and biobehavioral directions in promoting the health of men and boys - Courtenay, Will H. (New York : Brunner-Routledge, 2011)
"Men have specific gender-related influences that can affect their health and psychological well-being, and it is thus necessary for mental health practitioners to be knowledgeable in effective interventions for working with them. The purpose of this book is to provide a thorough foundation for understanding men health and risks and the differences between men. It will discuss effective, evidence-based strategies for practitioners to improve the health and well being of boys and men by drawing from a wealth of literature and research in a diverse array of disciplines, as well as from the authors original research designed specifically to examine gender and men's health"--Provided by publisher.
Gender and Ethnic Differences in Health Beliefs and Behaviors -- Masculinity and Gender Role Conflict : Influence on Men's Likelihood of Engaging in High-Risk Behaviors -- Measurement of Men's Help Seeking -- The Drive for Muscularity and Masculinity -- Part V: Reaching Men -- Introduction: Making Health Manly: Social Marketing and Men's Health -- Counseling Men About Their Health: An Evidence-Based Practice Guideline -- Designing Effective Programs and Services for College Men: Applying The Six-Point HEALTH Plan and Other Evidence-Based Strategies -- Part VI: Looking Forward -- Introduction: Teaming Up for the New Men's Health Movement -- A Global Perspective on the Field of Men's Health.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Men -- Health and hygiene; Health behavior; Electronic books